A barium-calcium silicate glass for use as seals in planar SOFCs - Namwong P. (2014)
A barium-calcium silicate glass for use as seals in planar SOFCs with a chemical composition of 40.78mol%BaO-4.36mol%CaO-0.62mol%Al2O3-0.83mol%B2O3-47.41mol% SiO2 was studied. Its coefficient of thermal expansion (CTE) between 25-640° C, glass transformation temperature (Tg) and softening temperature (Ts), determined by dilatometry, were 10.6x10-6°C-1, 646°C and 694°C, respectively. Isothermal devitrification heat treatment at 800°C, which is in the intermediate operation temperature range of planar SOFCs, revealed surface crystallization of various crystalline phases identified by XRD and SEM-EDS as BaAl2Si2O8 (hexacelsian), BaSiO3 and BaCa2Si3O9. Kinetics of devitrification followed the Johnson-Mehl-Avrami-Kolmogorov relationship with the Avrami exponent of 1.4. The overall CTE of the obtained glass-ceramic after the isothermal devitrification heat treatment was comparable to that of the glass. Adhesion test between the glass and the other components including YSZ and stainless steel grade AISI430 revealed that good union was achieved. The interfacial phenomena were studied by SEM-EDS and the mechanism of bonding were discussed.